Plant tissue and cell culture in Vietnam: forty-five years of development and the future - Thanh, Nguyen Duc (Academia Journal of Biology, 2020)
By 2020, plant tissue and cell culture in Vietnam had undergone 45 years of research and development. For nearly half a century, plant tissue and cell culture has been developed to its full potential, especially with the development of genetics, biochemistry and molecular biology. It has contributed significantly to basic and practical researches in our country. In addition to contributions to domestic science and technology, plant tissue and cell culture in Vietnam has also made impressive imprints in the development of plant tissue and cell culture in the world. In this review, I will summarize the process of formation, development and important achievements as well as the challenges and future prospects of this potential field in Vietnam to provide information for researchers, managers, graduate students and other interested readers.